2015
DOI: 10.1371/journal.pone.0144442
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Caloric Restriction on Chronic Kidney Disease in Rodent Models: A Meta-Analysis and Systematic Review

Abstract: BackgroundNumerous studies have demonstrated the life-extending effect of caloric restriction. It is generally accepted that caloric restriction has health benefits, such as prolonging lifespan and delaying the onset and progression of CKD in various species, especially in rodent models. Although many studies have tested the efficacy of caloric restriction, no complete quantitative analysis of the potential beneficial effects of reducing caloric intake on the development and progression of CKD has been publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Previous systematic reviews investigated the effect of CR on the development and progression of age-related chronic diseases in animal models [81][82][83] and humans, focusing on a limited number of health outcomes [84,85] or examining lifespan outcomes in cohorts not entirely representative of the general population [86]. Opposed to these previous studies, our systematic review was focused on the impact of CR on health predictors of longevity, disease risk factors and quality of life in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews investigated the effect of CR on the development and progression of age-related chronic diseases in animal models [81][82][83] and humans, focusing on a limited number of health outcomes [84,85] or examining lifespan outcomes in cohorts not entirely representative of the general population [86]. Opposed to these previous studies, our systematic review was focused on the impact of CR on health predictors of longevity, disease risk factors and quality of life in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that 60–80% caloric restriction (20–40% fewer calories than an ad libitum-fed group) may yield obvious effects, including a higher eGFR [ 22 , 23 ]. However, we did not detect an association between lower energy intake and a higher eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic renal disease may result from pathophysiological mechanisms affecting the glomerular, tubular, vascular and/or interstitial compartments of the kidney. As it progresses, chronic renal disease causes glomerular and tubulointerstitial lesions, with presence of inflammatory infiltrates that evolve to glomerular sclerosis and tubulointerstitial fibrosis [58][59][60][61][62]. Proteinuria is an important factor in this process.…”
Section: Discussionmentioning
confidence: 99%